Answered

Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Please help!

Write the sum, and then write an equivalent expression by collecting like terms and removing parentheses whenever possible.

a. -4 and 4b + 4
b. 3x and 1 -3x


Sagot :

Answer:

Does this problem have a picture, I just need to make sure I am seeing everything correctly thanks!

Step-by-step explanation:

a. -4 and 4b + 4 = 4b

-4 and 4b + 4 = -4 + (4b + 4) = 4b + (4 - 4) = 4b + 0 = 4b

b. 3x and 1 - 3x = 1

3x and 1 - 3x = 3x + (1 - 3x) = 1 + (3x - 3x) = 1 + 0 = 1

Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.